Identification of organic fouling on seawater membrane desalination (EN-12) - Tan, Joanne Man Ping (2017)
Due to the scarcity of freshwater, seawater desalination has become an important alternative as a source of freshwater. Seawater desalination using reverse osmosis has been widely adopted due to lower treatment costs with high productivity of clean water compared with other conventional desalination technologies. However, the effect of membrane fouling has been widely identified as a critical issue hindering smooth operation of the RO system. Fouling of the RO membrane by organic matter is one of the main concerns in natural waters especially in seawater. In this study, the fouling of RO membranes by dissolved organic matter, mainly biopolymer and humic substances with building blocks, were investigated. Fractions of biopolymer and humic acid from seawater were characterized by liquid chromatography – organic carbon detection (LC-OCD), fluorescence excitation-emission matrix and attenuated total reflectance - fourier transform infrared spectrometry (ATR-FTIR). Model organic foulants – commercial sodium alginate, bovine serum albumin and humic acid were used to relate between the actual organic feed and the synthetic feed. In addition to the characterization of organic foulants, a dead-end filtration system was adopted with a constant pressure operation mode to conduct a baseline study of the fouling rate for the fractions of BP and HS+BB and model foulants. The fouling rate was predicted from the permeate flux decline rate by each organic feed. The F-EEM and FTIR spectra of the BP and HS+BB fractions showed that there were some organic components which were not found in the model organic foulants. The results of the flux decline revealed that the model foulants had a greater flux drop compared to the actual fraction of BP and HS+BB. Additionally, due to its organic properties, the model foulant presented significant interactions due to the solution chemistry. Generally, commercial humic acid from Sigma Aldrich presented significant difference with the actual HS+BB fraction. This could be possibly because the humic acid was of terrestrial origin. BSA and polysaccharides displayed stronger characteristic of their organic species compared to the actual seawater fractions. This could have been the result of greater flux decline by the model foulants.